Klasifikasi Kebendaan Aset Kripto serta Perolehan Hak Kebendaannya Berdasarkan KUHP Perdata - Naufal Widi Adyawan (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The rapid development of the current era has given rise to various advances in the world of technology, one of which is marked by the presence of crypto assets. Crypto assets themselves have been widely used for various purposes in various countries, including Indonesia. However, of all the regulations regarding activities related to crypto assets, there is not a single regulation that explains the actual status of the property rights of these crypto assets. The purpose of writing this article is to determine the status of property rights and the acquisition of property rights from crypto assets. The type of research used is normative research by examining legal materials consisting of primary legal materials and secondary legal materials. Based on the results of this research, it was found that crypto assets can be said to be objects, in this case specifically intangible objects, movable objects, and some are consumable objects and non-consumable objects. According to the Civil Code, the method of obtaining the right is divided into several ways, namely claim, handover, inheritance, expiration, and withdrawal.